The influence of antithyroid drug discontinuation to the therapeutic efficacy of 131 I in hyperthyroidism - Kartamihardja, A. Hussein Sundawa; Massora, Stepanus (World Journal of Nuclear Medicine, 2016)
The influence of antithyroid drugs (ATDs) on the therapeutic efficacy of radioactive iodine in hyperthyroidism is still controversial. The aim of this study was to evaluate the effect of ATD discontinuation to the therapeutic efficacy of I-131 in hyperthyroidism patients with long-term ATD treatment. Retrospective study was done to 39 subjects with hyperthyroidism who had been treated with doses of 300 MBq radioactive iodine. The subjects were divided into three groups: Group I (n = 14) had been using ATDs for more than one year and discontinued more than three days; group II (n = 14) had been using ATDs for more than one year but discontinued only for three days or less, and group III (n = 11) has never been used any ATD before radioactive iodine treatment. There was a significant difference in the therapeutic efficacy after three months of radioactive iodine treatment between group I and group II (P = 0.018), group II and group III (P = 0.017), but not between group I and group III (P = 1.0). There was no observed difference on the therapeutic efficacy between the three groups at 6 months after radioactive iodine therapy (P = 0.143). Administration of ATDs more than 1 year without discontinuation decreased response of radioactive iodine treatment in 3 months follow-up. Discontinuation of ATDs for more than 3 days before radioactive iodine treatment is recommended.
Keywords: Antithyroid drug; hyperthyroidism; radioactive iodine